2022
DOI: 10.1177/15385744221130836
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course and Treatment of Symptomatic Spontaneous Isolated Superior Mesenteric Artery Dissection with Total True Lumen Occlusion

Abstract: Objective We retrospectively investigated the association between the imaging features of spontaneous isolated superior mesenteric artery dissection (SISMAD) accompanied by total true lumen occlusion and the clinical symptoms to identify the patients at high risk and establish personalized therapeutic options. Methods Among 261 patients with SISMAD, we selected 37 with Yun’s type III dissection; 35 patients underwent successful conservative management and 2 patients underwent exploratory laparotomy. After disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, several authors have reported that even in cases where the true lumen is occluded, as in Yun's type III, the prognosis is often good with conservative treatment and type IIb recovers spontaneously because of the absorption of false lumen thrombus, and conservative treatment should be considered. 21,23,[26][27][28] In our case, the true lumen of the SMA dissection site was narrowed but not completely occluded, and the contrast effect of the SMA main trunk distal to the dissection site was maintained. If our cases had been type III, we would have performed revascularization during the initial surgery.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, several authors have reported that even in cases where the true lumen is occluded, as in Yun's type III, the prognosis is often good with conservative treatment and type IIb recovers spontaneously because of the absorption of false lumen thrombus, and conservative treatment should be considered. 21,23,[26][27][28] In our case, the true lumen of the SMA dissection site was narrowed but not completely occluded, and the contrast effect of the SMA main trunk distal to the dissection site was maintained. If our cases had been type III, we would have performed revascularization during the initial surgery.…”
Section: Discussionmentioning
confidence: 48%
“…32 In type III SMAD, occlusion of the SMA restricts the collateral blood supply, which puts the patient at high risk of intestinal necrosis; thus, early intervention is generally recommended. 33 Based on our results, patients with type IIa SMAD often have the most obvious FLCs within the 1-month follow up after diagnosis, so it is necessary to strictly follow up and manage all patients during this period. For patients with rapid reduction of false lumen within the 1-month follow up, we could appropriately prolong the follow-up interval and reduce unnecessary CTA examination.…”
Section: Discussionmentioning
confidence: 71%